Обгрунтування конструктивних параметрів робочого органа розкидача мінеральних добрив - Кобець, А. С.; Науменко, М. М.; Пономаренко, Н. О.; Kobets, Anatoly; Naumenko, Nikolai; Ponomarenko, Natalia (КНТУ, 2015)
Розроблено технологічні параметрів машин для внесення мінеральних добрив відцентрового типу. З’ясована одна з можливих причин нерівномірності розсівання добрив розкидачами відцентрового типу. Виведені спрощені для інженерного застосування формули, що дають можливість обґрунтовувати конструкцію дискового розкидача добрив, який гарантовано покращує розсівання. Створено технічні засоби, а саме відцентрові диски з живильником, які впроваджені в серійне виробництво. The technological parameters of machines for mineral fertilizers centrifugal type. Found out one of the possible causes of uneven sieving fertilizer spreaders centrifugal type. We derive a simplified formula for the engineering application, which allow to justify the construction of disc fertilizer spreader that is guaranteed to improve dispersion. Developed technical means, namely the spreading discs with a feeder, which are introduced into production. The scientific bases of a substantiation of technological parameters of the machines. By mathematical modeling derived relationships that describe the patterns in the process that is carried out fertilizing machines and accessories, namely: - аcceleration of the centrifugal fertilizer dissipating body, wherein the vanes are angled to the horizontal plane and its radius; - мovement of fertilizers to the surface of the scattering body field applied to the general case, which includes their flight in atmospheric conditions. The laws of descent fertilizer spreading body and the nature of their distribution over the surface of the soil. With this in mind, the working body designed to make fertilizer and analytically grounded optimal values of its structural and kinematic parameters. The main factors that have a key influence on the performance of the machines.
Substantiation of the design features of the working body of the spreader mineral fertilizers
Keywords: внесення добрив; мінеральні добрива; якість розподілення; продуктивність машин; параметри розкидачів; fertilizer; fertilizers; quality allocation; performance cars; the parameters spreaders